2015
DOI: 10.1186/s40733-015-0012-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic studies of FOXP3 in asthma and allergy

Abstract: Multiple factors interact to trigger allergic diseases, including individual genetic background and factors related to the environment such as exposure to allergens, air pollution and respiratory infections. The FOXP3 transcription factor is constitutively expressed in CD4+CD25+FOXP3+ regulatory T cells (Tregs) and is critical for the maintenance of immune homeostasis. For example, FOXP3 is responsible for the suppression of the Th2 response following exposure to allergens. Studies have shown that expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…Additional meta‐analyses of other SNPs or haplotype are required to give more comprehensive insight into the role of FOXP3 polymorphisms in the susceptibility to allergic rhinitis. Considering the close functional link between asthma/allergy and FOXP3 protein or CD4 + CD25 + FOXP3 + regulatory T cells (Tregs) (Marques et al., ), it is possible that certain or unidentified variations of the FOXP3 gene are involved in an increased allergic rhinitis risk by modulating the biological properties of FOXP3 protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional meta‐analyses of other SNPs or haplotype are required to give more comprehensive insight into the role of FOXP3 polymorphisms in the susceptibility to allergic rhinitis. Considering the close functional link between asthma/allergy and FOXP3 protein or CD4 + CD25 + FOXP3 + regulatory T cells (Tregs) (Marques et al., ), it is possible that certain or unidentified variations of the FOXP3 gene are involved in an increased allergic rhinitis risk by modulating the biological properties of FOXP3 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Natural CD4 + CD25 + T‐regulatory cells primarily expressed FOXP3 protein, which is capable of influencing the immune responses through modulating the proliferation, cytokine production and suppressive activity of T cells (Hori et al., ; Williams & Rudensky, ; Paik et al., ; Park et al., ; Pesenacker et al., ). The functional impairment of FOXP3 protein may be implicated in the pathogenesis of several human clinical disorders or syndromes, such as immune dysregulation, polyendocrinopathy, enteropathy, X‐linked syndrome (IPEX), X‐linked autoimmunity allergic dysregulation (XLAAD) and malignancies (L. Zhang et al., ; Bottema et al., ; Benayoun et al., ; Guo et al., ; Y. Zhang et al., ; Marques et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the regulatory mechanism of gene expression is controlled by genomic polymorphisms. Single nucleotide polymorphisms (SNPs) in FOXP3 have been associated with various diseases [ 11 ], including asthma [ 12 ], preeclampsia [ 13 ], systemic lupus erythematosus [ 14 ], autoimmune thyroid disease [ 15 ], lung cancer [ 16 ], breast cancer [ 17 ], and colorectal cancer [ 18 ]. Recently, several studies reported that FOXP3 SNPs are associated with allograft outcomes after renal transplantation, but there is ongoing debate over whether FOXP3 SNPs have a positive or negative association with allograft outcomes [ 19 20 21 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This polymorphisms may presumably change gene expression by modifying the binding specificity of transcription factors to their binding sites and by altering the kinetics of transcription initiation (Hanel et al 2011 ). Moreover, SNPs in FOXP3 gene can influence miRNA, gene splicing or encoded protein structure and activity (Marques et al 2015 ). We analyzed three of the known five polymorphisms the promoter region of FOXP3: − 2383C/T (rs3761549), − 3279G/T (rs3761548), and − 3499T/C (rs3761547).…”
Section: Discussionmentioning
confidence: 99%